Advances in Signal Processing and Intelligent Recognition Systems Proceedings of Second International Symposium on Signal Processing and Intelligent Recognition Systems (SIRS-2015) December 16-19, 2015, Trivandrum, India - Thampi, Sabu M.; Bandyopadhyay, Sanghamitra; Krishnan, Sri.; Li, Kuan-Ching.; Mosin, Sergey; Ma, Maode; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This Edited Volume contains a selection of refereed and revised papers originally presented at the second International Symposium on Signal Processing and Intelligent Recognition Systems (SIRS-2015), December 16-19, 2015, Trivandrum, India. The program committee received 175 submissions. Each paper was peer reviewed by at least three or more independent referees of the program committee and the 59 papers were finally selected. The papers offer stimulating insights into biometrics, digital watermarking, recognition systems, image and video processing, signal and speech processing, pattern recognition, machine learning and knowledge-based systems. The book is directed to the researchers and scientists engaged in various field of signal processing and related areas. .
Biometrics, Digital Watermarking, Recognition Systems -- Image, Video Processing -- Signal, Speech Processing -- Pattern Recognition, Machine Learning, Knowledge-Based Systems -- WorkshopA on Advances in Image Processing, Computer Vision, and Pattern Recognition (IWICP-2015) -- Workshop on Signal Processing for Wireless and Multimedia Communications (SPWMC'15).
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing